Persepsi keterlibatan ayah dalam pengasuhan dan masalah eksternalisasi pada remaja - Maslina, Nur; Syakarofath, Nandy Agustin; Karmiyati, Diah; Widyasari, Dian Caesaria (Universitas Brawijaya, 2022)
Teenagers are vulnerable to experiencing an identity crisis. This crisis encourages some adolescents to externalize their problems by engaging in deviant behaviors. One factor that drives externalizing problems in adolescents is their perception of their father’s involvement. This study aims to determine the role of adolescents’ perception of their father’s involvement in their externalizing problems. The participants in this study were 498 Muhammadiyah Middle School students in several cities in East Java who were selected based on a simple random sampling technique. Adolescents’ perception of their father’s involvement inversely predicted their externalizing problems. Adolescents with a higher perception of their father’s involvement tended to have lower externalizing problems. Keywords: adolescents, father’s involvement, externalizing problem